Rifampicin and ofloxacin dual therapy as an adjunct to standard MB-MDT in the management of nodulo-ulcerative lepromatous leprosy with histoid-like features: a case report - H, Varun; Singh, Adarshlata; Madke, Bhushan; Mittal, Anurag (Frontiers in Medicine, 2025)
Leprosy, induced by Mycobacterium leprae, and in some cases, Mycobacterium lepromatosis, remains an important public health issue in endemic regions despite ongoing elimination efforts. Histoid Hansen’s disease, a variant of lepromatous leprosy, is characterised by shiny, well-defined nodules and a heavy acid-fast bacillary load. We present a case of a 50-year-old male agricultural worker from rural central India presenting during a community health camp with multiple cutaneous nodules clinically suggestive of histoid leprosy. Slit-skin-smears (SSS) revealed abundant needle-shaped acid-fast bacilli, with numerous globi, whereas histopathological examination of a lesional biopsy supported the diagnosis of lepromatous leprosy (LL). This report presents a novel two-step treatment approach that is aimed at rapidly reducing infectivity using a 28-day course of rifampicin and ofloxacin (RO therapy), followed by initiation of multi-bacillary multidrug therapy (MB-MDT) to ensure sustained bacillary clearance. Repeat SSS demonstrated fragmented and granular acid-fast bacilli, indicating effective bactericidal activity. This case underscores the need for vigilant surveillance, early identification, and potential strategies to combat relapses and drug-resistant strains in the post-elimination era.